2017
DOI: 10.11648/j.ajls.20170505.13
|View full text |Cite
|
Sign up to set email alerts
|

Initial Growth Responses of Multipurpose Tree Species Under Termite Infested Areas at Mana Sibu District of West Wollega Zone, Oromia Regional State, Ethiopia

Abstract: An experimental study was carried out at Mana Sibu district of West Wollega zone, Oromia Regional state, Ethiopia to evaluate and select multipurpose tree species for rehabilitation of termite degraded area. Seven tree species (Cordia africana, Melia azedrach, Albizia gummifera, Jacaranda mimosifolia, Acacia mearnsii, Acacia albida and Croton macrostychus) were used for the experiment and both organic and inorganic fertilizers were also used as a treatment to support the seedlings for initial survival. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Survival rate varies between and within species(Sinclair and Coe, 2019)and from site to site(Davis and Pinto, 2021). Seedlings survival was high during early plantations(Gebre et al, 2022)and stabilizes after the second year(Sukhbaatar et al, 2020).In the second and third years, survival rate declined slightly and remained unchanged in the fourth year(Shi et.al., 2019).Similarly, the overallsurvival ratein our study decreased from 100 to45.8%twenty months after planting. Different survival rate values had reported for the same tree species in different time and areas.Authors such as Talema et al, (2019);Cheneke and Abdella, (2021); Gebre et al, (2022)reported relatively poor survival rate (37-68%) values of G. robusta and itagreeswith thecurrent study(56.3%).…”
supporting
confidence: 64%
“…Survival rate varies between and within species(Sinclair and Coe, 2019)and from site to site(Davis and Pinto, 2021). Seedlings survival was high during early plantations(Gebre et al, 2022)and stabilizes after the second year(Sukhbaatar et al, 2020).In the second and third years, survival rate declined slightly and remained unchanged in the fourth year(Shi et.al., 2019).Similarly, the overallsurvival ratein our study decreased from 100 to45.8%twenty months after planting. Different survival rate values had reported for the same tree species in different time and areas.Authors such as Talema et al, (2019);Cheneke and Abdella, (2021); Gebre et al, (2022)reported relatively poor survival rate (37-68%) values of G. robusta and itagreeswith thecurrent study(56.3%).…”
supporting
confidence: 64%